2021
DOI: 10.1002/ejlt.202000091
|View full text |Cite
|
Sign up to set email alerts
|

Crude Wax Extracted from Rice Bran Oil Improves Oleogel Properties and Oxidative Stability

Abstract: Crude wax extracted from rice bran oil (RBO) is used to improve the oleogel properties and oxidative stability of RBO. The effect of crude rice bran wax (CrBW) on the formation characteristics and oxidative stability of oleogels is discussed. The results show that oleogels can be formed with 7.0 wt% CrBW at 20 °C. As the concentration of CrBW increases from 7.0 to 11.0 wt%, the hardness and solid fat content (SFC) of the oleogels increase significantly, and the oleogels are primarily β' crystals. Moreover, ole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Although 6% w/w of neither wax provided self-standing gels but, at 12% CW and BW successfully showed self-standing gels with an improved gel network. This indicated that with the increase in oleogelator concentration, the oil binding increased leading to a lower OL percentage which also coincides with the findings of Wang et al (2021).…”
Section: Oil Loss and Gel Strengthsupporting
confidence: 87%
See 1 more Smart Citation
“…Although 6% w/w of neither wax provided self-standing gels but, at 12% CW and BW successfully showed self-standing gels with an improved gel network. This indicated that with the increase in oleogelator concentration, the oil binding increased leading to a lower OL percentage which also coincides with the findings of Wang et al (2021).…”
Section: Oil Loss and Gel Strengthsupporting
confidence: 87%
“…This indicated that with the increase in oleogelator concentration, the oil binding increased leading to a lower OL percentage which also coincides with the findings of Wang et al . (2021).…”
Section: Resultsmentioning
confidence: 99%
“…Oleogel is gradually attracting attention as a semi-solid substance form with low saturated fatty acid content and no trans fatty acids. It prevents health problems caused by the high content of saturated fatty acids in traditional plastic fat [5] . Additionally, oleogel can make food have great color, flavor, texture, and stability [6] , and can be used to replace traditional plastic fat in foods.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al. [ 47 ] tested the SFC of oleogels made with crude rice bran wax at weight percentages of 7.0%, 9.0%, and 11.0%. At 30°C, SFCs were roughly 1.8%, 4.7%, and 7.4%; at 35°C, they were 1%, 3%, and 6.5%.…”
Section: Resultsmentioning
confidence: 99%
“…SFC values of OP ranged from 1.40% to 3.60% at 30 C were discovered by Kim et al [46] to be approximately 4.5% and 9%, respectively. Wang et al [47] tested the SFC of oleogels made with crude rice bran wax at weight percentages of 7.0%, 9.0%, and 11.0%. At 30 • C, SFCs were roughly 1.8%, 4.7%, and 7.4%; at 35 • C, they were 1%, 3%, and 6.5%.…”
Section: Physical Properties Of Oleogelsmentioning
confidence: 99%